Prevalence of High and Low-Level Mupirocin Resistance in Clinical Isolates of Staphylococcus Aureus from Skin and Soft Tissue Infection: Life Sciences -Microbiology - Subhash Mohite, Miss. Aishwarya; V. Shinde, Dr. Ravindra; S. Patil, Dr. Deepak; T. Mohite, Dr. Shivaji; R. Patil, Dr. Satish; R. Shinde, Dr. Anjali; B. Shinde, Dr. Sandeep (International Journal of Life Science and Pharma Research, 2023)
The skin has an extremely diverse ecology of organisms that may produce infection. The clinical manifestations of skin and soft tissue infection(SSTIs) culminate in a two-step process involving invasion and the interaction of bacteria with host defenses. Approximately 7% to 10% of hospitalized patientsare affected by SSTIs. Mupirocin has been used to treat skin infections and eradicate the nasal carriage of MRSA. Our aim is to estimate the prevalence of lowand high-level Mupirocin resistance among the clinical isolates of Staphylococcus aureus from skin and soft tissue infection. The study was conducted in theDepartment of Microbiology, Krishna Institute of Medical Sciences, Krishna Hospital and Medical Research Centre, Karad, District- Satara. Specimen collectionand processing of samples were performed as per standards. The Kirby -Bauer disc diffusion method was used for the sensitivity to common antibioticsrecommended Clinical and Laboratory Standard Institute (CLSI 2021). Mupirocin resistance was detected using 5μg and 200μg Mupirocin discs to determineLow and High -level resistance. 135 Staphylococcus aureus isolates were obtained from patients admitted to various medical, surgical, and intensive care unitsand patients attending outpatient departments. Out of 415 clinically suspected cases of skin and soft tissue infection, 91.33% were culture positive, and 8.67%were culture negative. Out of 379 microorganisms, 44.06% were Gram-positive cocci, 27.44% were Gram negative bacilli, 24.27% were Gram negative cocci,and 14.22% were Gram-positive bacilli. Out of 167 Gram positive cocci, 135 (80.84%) were Staphylococcus aureus, 22 (13.17%) were Coagulase NegativeStaphylococcus and 10 (5.99%) were Micrococcus. We conclude that the prevalence of Staphylococcus aureus was 32.53%, among which Mupirocin high and lowlevelresistance was 5.92% and 7.41%, respectively.